2019
DOI: 10.1063/1.5089637
|View full text |Cite
|
Sign up to set email alerts
|

A domain-based local pair natural orbital implementation of the equation of motion coupled cluster method for electron attached states

Abstract: This work describes a domain-based local pair natural orbital (DLPNO) implementation of the equation of motion coupled cluster method for the computation of electron affinities (EAs) including single and double excitations. Similar to our earlier work on ionization potentials (IPs), the method reported in this study uses the ground state DLPNO framework and extends it to the electron attachment problem. While full linear scaling could not be achieved as in the IP case, leaving the Fock/Koopmans’ contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 105 publications
2
85
0
Order By: Relevance
“…Similar conclusions hold for the state‐specific PNO implementation as well as for the state averaged PNO EOM implementation of Valeev . Our own STEOM implementation depends on ground state PNOs, for which standardized parameter sets guaranteeing a certain accuracy are available, and it has been shown that the error in the ground state computation and in the subsequent IP/EA calculations can also be kept below similar limits . The question of accuracy is most complicated for multilayer embedding methods.…”
Section: Benchmarkssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar conclusions hold for the state‐specific PNO implementation as well as for the state averaged PNO EOM implementation of Valeev . Our own STEOM implementation depends on ground state PNOs, for which standardized parameter sets guaranteeing a certain accuracy are available, and it has been shown that the error in the ground state computation and in the subsequent IP/EA calculations can also be kept below similar limits . The question of accuracy is most complicated for multilayer embedding methods.…”
Section: Benchmarkssupporting
confidence: 65%
“…A DLPNO implementation of the IP–EOM is straightforward and requires only a few ground state intermediates in the ground state PNO basis to reach near linear scaling. The EA–EOM equations are more problematic because of the truncation of the leading term, as already noted by Krylov and coworkers . Since the leading Fock term cannot be associated to any occupied orbital, it has to be kept in the canonical basis, while for terms with a single occupied label, it is advantageous to introduce a new set of ground state PNOs.…”
Section: Algorithmic Approximationsmentioning
confidence: 99%
“…We have recently extended the EOM-CCSD method in the framework of the domain-based pair natural orbitals (DLPNO). 63 On the basis of the performance of the EOM-DLPNO-CCSD method in calculating electron affinities, it is expected that implementation of the relevant STEOM-DLPNO-CCSD method will be much more efficient than the respective bt-PNO-STEOM-CCSD method. Hence, it is expected that the above-reported timings will be drastically decreased toward values that are more in line with the DFT performance.…”
Section: Evaluating the Performance Of Steom-cc Td-dft And δScf/dftmentioning
confidence: 99%
“…However, wave‐function based methods converge very slowly with respect to the basis set size and are impractical to be used for large anions. The newly developed domain‐based local pair natural orbital (DLPNO) implementation of the equation of motion coupled cluster (EA‐EOM‐DLPNO‐CCSD) method can be applied to electron attached states of large molecules with systematic controllable accuracy. We have recently developed a QM/MM protocol based on EA‐EOM‐DLPNO‐CCSD method, which can treat the ground and excited states of the solvated anion on an equal footing and can reproduce the experimentally reported rate of reduction of solvated nucleobases .…”
Section: Introductionmentioning
confidence: 99%